Clinical classification and treatment of cesarean scar pregnancy. Issue 4 (2nd February 2017) - Zhang, Hongwen; Huang, Jingrui; Wu, Xianqing; Fan, Hong; Li, Han; Gao, Tian
Abstract: Aim: Embryo implantation in a cesarean scar resulting in a cesarean scar pregnancy (CSP) is a special form of ectopic pregnancy. The aim of this article is to present our clinical classification and therapeutic strategy for CSP and to assess the efficacy, safety, and social benefits. Methods: We categorized CSP as either risky or stable. Risky CSP have a high risk of severe hemorrhage and should be treated immediately, while stable CSP patients have neither obvious vaginal bleeding nor significantly elevated serum β‐human chorionic gonadotrophin (β‐hCG). According to the thickness of the myometrial wall between the sac and the bladder and the location of the gestational sac, risky CSP were classified into three types and the thinner myometrial wall type (type I) was divided into three subtypes. Four treatment categories were applied to the corresponding types and subtypes of CSP. A total of 331 patients with CSP in our hospital were studied. The study group ( n = 81) was treated based on our classification and optimized treatment system, while the control group ( n = 250) underwent the conventional methods. We assessed the efficacy, safety, and social benefits of our classification and optimized treatment system. Results: The values of intraoperative blood loss, operative time, hospital stay, and hospital cost in the study group were significantly lower than those in the control group ( P < 0.05). Suction curettage was more frequently used in the study group ( P < 0.005). Conclusion: Our clinical classification system and therapeutic strategy provide an effective and safe way to treat CSP patients resulting in reduced intraoperative bleeding, operative time, hospital days, and hospital cost.